2021
DOI: 10.1002/pd.6051
|View full text |Cite
|
Sign up to set email alerts
|

Fetal open spinal dysraphism repair through a mini‐hysterotomy: Influence of gestational age at surgery on children's ability to walk

Abstract: Objective:To analyze the impact of gestational age (GA) at the time of fetal open spinal dysraphism (OSD) repair through a mini-hysterotomy on the ability of children to walk. Methods:Children who underwent in utero repair of OSD and had formal neurological assessment after 2.5 years of age were compared regarding their ability to walk in relation to pre-surgical predictors.Results: Sixty-nine children fulfilled the inclusion criteria. Among them, 63.7% (44/ 69) were able to walk with or without orthesis. Feta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
2
0
0
Order By: Relevance
“…The risk of prematurity was significantly greater in the prenatal group, with a greater frequency of extremely premature infants. Compared to previously reported rates for prenatal surgery, the rate found in the present study (79%) was similar to that reported for classic open surgery (74%) and for mini-hysterotomy (76.9%), but higher than rates reported for microneurosurgery (52.4%) and endoscopy (71.8%) [19,22,25].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The risk of prematurity was significantly greater in the prenatal group, with a greater frequency of extremely premature infants. Compared to previously reported rates for prenatal surgery, the rate found in the present study (79%) was similar to that reported for classic open surgery (74%) and for mini-hysterotomy (76.9%), but higher than rates reported for microneurosurgery (52.4%) and endoscopy (71.8%) [19,22,25].…”
Section: Discussionsupporting
confidence: 85%
“…PROM was the most important gestational complication, occurring in 48% of cases in the prenatal group. This rate is close to that of 46% described in the classic MOMS study with a uterine incision of 6.0 to 8.0 cm, but higher than that described for the mini-hysterotomy technique (28.3%), with an incision of 2.5 to 3.5 cm, and for microneurosurgery (19.0%) with an incision of 1.5 to 2.0 mm [1,18,25]. For open surgery, the risk of PROM seems lower when the uterine incision is smaller.…”
Section: Discussionsupporting
confidence: 80%
“…The risk of prematurity was signi cantly greater in the prenatal group, with a greater frequency of extremely premature infants. Compared to previously reported rates for prenatal surgery, the rate found in the present study (79%) was similar to that reported for classic open surgery (74%) and for minihysterotomy (76.9%), but higher than rates reported for microneurosurgery (52.4%) and endoscopy (71.8%) [19,22,25].…”
Section: Discussionsupporting
confidence: 85%
“…PROM was the most important gestational complication, occurring in 48% of cases in the prenatal group. This rate is close to that of 46% described in the classic MOMS study with a uterine incision of 6.0 to 8.0 cm, but higher than that described for the mini-hysterotomy technique (28.3%), with an incision of 2.5 to 3.5 cm, and for microneurosurgery (19.0%) with an incision of 1.5 to 2.0 mm [1,18,25]. For open surgery, the risk of PROM seems lower when the uterine incision is smaller.…”
Section: Discussionsupporting
confidence: 81%